Modern Law Aspect on Procedural Decision of Sultan Adam Law - Hasan, Ahmadi; Hafidzi, Anwar; Zaidah, Yusna (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
The main focus of this research was analyzing the normative procedural decision of Sultan Adam Law which was applied by Sultan Adam during 1835 AD. Its emergence was for strengthening Islam Aqeedah for its believers and clinging on to Syafii Madhhab. Sultan Adam Law was remarkable to scrutinize, especially when associated with the modern law aspect. By employing the law history approach, this research attempted to respond to Sultan Adam Law procedural decision document issues which were associated with the modern law aspect. It could be seen through several sides such as political law, law substance, arrangement system as well as procedural aspect. The research also responded on how several factors explained Sultan Adam Law included in modern law. Based on the analysis result, it could be concluded that Sultan Adam Law was a written law decision which its existence in Banjarese people contained principles and legal norms as well as several procedural law decisions in a modern way. Although it was simple systematics which did not classify based on article and section, it contained several decision or principles and legal norms.